2014
DOI: 10.1128/iai.01710-14
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Hyaluronidase Is a CodY-Regulated Virulence Factor

Abstract: Staphylococcus aureus is a Gram-positive pathogen that causes a diverse range of bacterial infections. Invasive S. aureus strains secrete an extensive arsenal of hemolysins, immunomodulators, and exoenzymes to cause disease. Our studies have focused on the secreted enzyme hyaluronidase (HysA), which cleaves the hyaluronic acid polymer at the ␤-1,4 glycosidic bond. In the study described in this report, we have investigated the regulation and contribution of this enzyme to S. aureus pathogenesis. Using the Nebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 63 publications
3
78
0
Order By: Relevance
“…Given that S. aureus systemic infections can readily arise from skin or mucosal sites, it is reasonable to infer that the active invasion of host tissue is a key facet of S. aureus pathogenicity. Consistent with this view, S. aureus hysA mutants exhibit a hypovirulent phenotype in models of acute pulmonary and cutaneous infection (22,23). In addition, hyaluronidases from numerous Gram-positive pathogens have been shown to promote tissue penetrance of bacteria, toxins, and large-molecular-mass dyes in the vicinity of the challenge site (25,57).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Given that S. aureus systemic infections can readily arise from skin or mucosal sites, it is reasonable to infer that the active invasion of host tissue is a key facet of S. aureus pathogenicity. Consistent with this view, S. aureus hysA mutants exhibit a hypovirulent phenotype in models of acute pulmonary and cutaneous infection (22,23). In addition, hyaluronidases from numerous Gram-positive pathogens have been shown to promote tissue penetrance of bacteria, toxins, and large-molecular-mass dyes in the vicinity of the challenge site (25,57).…”
Section: Discussionmentioning
confidence: 52%
“…Within the context of intense homeostatic stress such as nutrient deprivation, HysA might play a multifunctional role as a mediator of biofilm dispersal and tissue invasion, which are both vital to a recolonization effort. Coupling the proposed HysA behaviors with nutritional distress, we recently showed that the global regulator CodY represses hysA expression (22) in response to nutrient levels in the cell. Thus, CodY could control biofilm dissemination in a nutrient-dependent manner and facilitate S. aureus survival when facing a resource-depleted environment (i.e., nutritional immunity [52]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice infected with mutant strains carrying mutation of the CodY binding box exhibited a 4-log-unit reduction in bacterial burden in their lungs, reduced lung pathology and increased levels of pulmonary hyaluronic acid, compared to mice infected with the wild-type, parent strain. These results can give insight into the possible reduction of the strain virulence, especially in patients with lung infection (25).…”
Section: Hyaluronidasementioning
confidence: 99%
“…The transcription of S. aureus hyaluronidase, encoded by hysA, is controlled by the accessory gene regulator (Agr) quorum-sensing system (86,87). Work by Ibberson et al (88) suggests that B (as well as CodY) downregulates agr and therefore indirectly and negatively controls hyaluronidase activity in S. aureus. Based on the observation that sigB and codY mutants express higher levels of hyaluronidase activity, hysA is proposed to be under direct positive control by the effectors of Agr and negatively modulated by CodY and B (88).…”
Section: In Metabolism Of Harmful Components and Utilization Of Diffementioning
confidence: 99%